Perlindungan Hukum terhadap Notaris yang Beritikad Baik Membuat Akta Jual Beli Saham dalam Kasus Tindak Pidana Pencucian Uang - Rahmat, Andi Muhammad (University of Jember, 2019)
This study discusses the legal protection against a notary who has good faith to make the contract of sale with stock in this case of criminal money laundering. To this extent, the study examines the legal protection for notaries who are eligible to be victims from the money laundering cases caused by user services. This study uses normative legal research with statute, philosophical and historical approaches. This study finds that legal protection for notaries referred to Articles 66 and 66A of the Notary Act is essentially tended to internal or administrative measures. Nevertheless, notaries have verschoningsrecht or the right to renegade, another instrument for legal protection in undertaking the Notary Act. The legal protection concept for notaries with the determinate profession on the informant side has been determined limitedly under Article 17 paragraph 1 of the Money Laundering Act. Keywords: Construction, Legal Protection, Notary, Money Laundering